Primum vivere ... industrial change, job destruction and the geographical distribution of unemployment - Francesco Pastore (IZA Journal of European Labor Studies, 2012)
This paper aims to provide a frame of mind to understand the link between structural change and regional unemployment, and, based on it, to survey the most recent literature. An overly optimistic view on the ability of the adjustment mechanism to generate convergence in local unemployment rates has long neglected the question of how regional imbalances arise in the first place. The availability of new longitudinal data sets allows us looking again at this issue with a fresh look, starting from patterns of reallocation among labour market statuses. The main conclusion of recent research is that high unemployment regions have a higher, not a lower rate of reallocation; this suggests, in turn, that they do not suffer from low job creation, but, rather, from high job destruction, and this is because of the low competitiveness of any economic activity. Our findings sound as a renowned justification of the need for demand side policy, especially aimed at increasing the life expectancy of private businesses in high unemployment regions.
Keywords: J6; P2; R1; R23; 330; structural change; labour turnover; regional unemployment; new economic geography; EU regional policy; Strukturwandel; Regionaler Arbeitsmarkt; Personalabbau; Arbeitsmobilität; Wirtschaftliche Anpassung; Welt